Penurunan Kadar BOD, COD, dan Total Coliform dengan Penambahan Biokoagulan Biji Pepaya (Carica papaya L) (Studi pada Limbah Cair Domestik Industri Baja di Surabaya Tahun 2020) - Dinda Yully Lestari; Darjati Darjati; Marlik Marlik (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Domestic wastewateris wastewaterthat is from residential businesses or activities, restaurants, offices, businesses, apartments and dormitories. Preliminary test result against BOD, COD, and Total Coliform in domestic wastewaterof steel industry in Surabaya did not qualify in which according to Regulation of Minister of Environment and Forestry in Republic of Indonesia Number 68 of 2016, the requirements were 63 mg/l, 189 mg/l and 13,000 CFU/100ml. Treatment that could be conducted was coagulation-flocculation with the addition of biocoagulant of papaya seed. Moreover, the purpose of this study was in order to analyze the reduction in BOD, COD, and Total Coliform level in domestic wastewaterof steel industry in Surabaya by adding biocoagulant of papaya seed (Carica papaya L). Type of this research was a pure experimental research with pretest-posttest control group design. Object of this research was domestic wastewater in one of steel industries in Surabaya, East Java Province, Indonesia. The dosage variations were 1 gram, 2 grams and 3 grams and 0 gram as a control with replication as much as 6 times. Thus, it was obtained 24 sample size. The results of BOD, COD, and Total Coliform before and after the addition of papaya seed(Carica papaya L)biocoagulant were analyzed by using paired t test and probit test. The results showed thatBOD, COD and Total Coliform levels in domestic wastewater of steel industry in Surabaya after having treatment reduced. The highest percentage in dose of 3 gr could reduce BOD and COD level until 93% and Total Coliform in 66%. The optimum dose in reducing BOD and COD levels were 3,629 gr/l and 3,109 gr/l. Furthermore, coagulation-flocculation wastewater treatment by using biocoagulant of papaya seed could reduce BOD, COD, and Total Coliform levels. Thus, for steel industry, it was necessary to conduct pre-treatmentof coagulation-flocculation treatment against domestic wastewater by using biocoagulant of papaya seed before being dumped into water bodies.